COMPARATIVE STUDY OF RETROGRADE DISTAL FEMORAL NAILING AND DISTAL FEMORAL PLATING IN EXTRA ARTICULAR DISTAL FEMUR FRACTURES - Vivek Phanswal; Mohammad Shuaib (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Distal femoral fractures are among challenging orthopedic injuries. Anatomical Distal Femoral locked plating and retrograde nailing are now method of choices of fracture fixation in such patients. Purpose of present study was to compare anatomical distal femur locked plating and retrograde intramedullary nailing for treatment of extra articular distal femur fractures.Materials and Methods: A prospective randomized study including 38 patients of extra articular distal femur fractures was conducted in the Department of Orthopedic surgery. Patients were divided in two groups by random allocation. Patients of group I (20 patients) were treated by distal femoral locked plating and group II (18 patients) by retrograde distal femoral nailing using standard technique.Results: The mean age of group I and group II were 52.5±16.8Years & 48.7±12.4 years respectively. The female – male ratio for both groups was matched (p=.075). The time of full weight bearing was significantly (p=0.004) less in nailing group. Bone union was seen earlier in group II (DFN) and it came to be statistically significant (p value-0.0006). Knee pain was present in 42.86% of patients in group II and it came out to be statistically significant (p